2008
DOI: 10.1128/jvi.01219-08
|View full text |Cite
|
Sign up to set email alerts
|

Topology and Membrane Anchoring of the Coronavirus Replication Complex: Not All Hydrophobic Domains of nsp3 and nsp6 Are Membrane Spanning

Abstract: Coronaviruses express two very large replicase polyproteins, the 16 autoproteolytic cleavage products of which collectively form the membrane-anchored replication complexes. How these structures are assembled is still largely unknown, but it is likely that the membrane-spanning members of these nonstructural proteins (nsps) are responsible for the induction of the double-membrane vesicles and for anchoring the replication complexes to these membranes. For 3 of the 16 coronavirus nsps-nsp3, nsp4, and nsp6-multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 66 publications
6
187
0
Order By: Relevance
“…Consistently, membrane association has been demonstrated for the nsp3, nsp4 and nsp6 proteins of SARS-CoV [41,42,43] and MHV [42,43,44,45]. Both nsp3 and nsp4 become N -glycosylated upon insertion into the membranes of the endoplasmic reticulum (ER) [42,43,44].…”
Section: Coronavirus Nonstructural Proteinsmentioning
confidence: 75%
“…Consistently, membrane association has been demonstrated for the nsp3, nsp4 and nsp6 proteins of SARS-CoV [41,42,43] and MHV [42,43,44,45]. Both nsp3 and nsp4 become N -glycosylated upon insertion into the membranes of the endoplasmic reticulum (ER) [42,43,44].…”
Section: Coronavirus Nonstructural Proteinsmentioning
confidence: 75%
“…The transmembrane domain is inserted into the endoplasmic reticulum (ER) membrane co-translationally and plays an important scaffolding role for the replication transcription complex [9]. Recently, it was shown that three transmembrane domains were predicted for the SARS-CoV nsp 3 but only two were found to span the ER membrane orienting the protease domain of nsp 3 on the cytoplasmic side where viral replication occurs [13,15]. In murine hepatitis virus (MHV), five transmembrane domains were predicted but only two domains were found to span the membrane, also locating the protease domain on the cytoplasm side [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that three transmembrane domains were predicted for the SARS-CoV nsp 3 but only two were found to span the ER membrane orienting the protease domain of nsp 3 on the cytoplasmic side where viral replication occurs [13,15]. In murine hepatitis virus (MHV), five transmembrane domains were predicted but only two domains were found to span the membrane, also locating the protease domain on the cytoplasm side [13,15]. Our sequence data for IBV predicts four transmembrane domains within nsp 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RdRp or nascent viral RNA has not been detected inside DMVs, and ultrastructural analysis could not confirm any connection between the DMV interior and the cytoplasm (38), raising questions about the import and export of ribonucleotide precursors and produced RNAs exported from RNA synthesis areas (44). The coexpression of the SARS-CoV transmembrane nonstructural proteins nsp3, nsp4, and nsp6 resulted in the formation of CMs and DMVs (45), suggesting a function in the biogenesis of the membranous replicative structures, and also in the anchoring of the RTC (4648). …”
Section: Role Of Double-membrane Vesiclesmentioning
confidence: 99%